Effectiveness of a group educational intervention - prolact - in primary care to promote exclusive breastfeeding: a cluster randomized clinical trial - María Jesús Santamaría- Martín; Susana Martín-Iglesias; Christine Schwarz; Milagros Rico-Blázquez; Julián Alexander Portocarrero-Nuñez; Laura Diez-Izquierdo; Laura Llamosas-Falcón; Ricardo Rodríguez-Barrientos; Isabel Del-; Grupo PROLACT (BMC, 2022)
Abstract Background The rates of exclusive breastfeeding at 6 months in Spain are far from recommended by the World Health Organization, which is 50% by 2025. Evidence of the effectiveness of group interventions in late postpartum is limited. The objective of this study was to evaluate the effectiveness of the PROLACT group educational intervention for increasing the proportion of mother-child dyads with exclusive breastfeeding at 6 months compared to the usual practice in primary care. Method Multicentre cluster randomized clinical trial. A total of 434 mother-child dyads who breastfed exclusively in the first 4 weeks of the children's life and agreed to participate were included. The main outcome was exclusive breastfeeding at 6 months. Secondary variables were type of breastfeeding, reasons for abandonment, degree of adherence and satisfaction with the intervention. To study the effectiveness, the difference in the proportions of dyads with exclusive breastfeeding at 6 months was calculated, and the relative risk (RR) and number needed to treat (NNT) were calculated with their 95% CIs. To study the factors associated with the maintenance of exclusive breastfeeding at 6 months, a multilevel logistic regression model was fitted. All analyses were performed to intention to treat. Results The percentage of dyads with exclusive breastfeeding at 6 months was 22.4% in the intervention group and 8.8% in the control group. PROLACT intervention obtained an RR =2.53 (95% CI: 1.54-4.15) and an NNT = 7 (95%CI: 5-14). The factors associated with exclusive breastfeeding at 6 months were the PROLACT intervention, OR = 3.51 (95%CI: 1.55-7.93); age > 39 years, OR = 2.79 (95%CI: 1.02-7.6); previous breastfeeding experience, OR = 2.61 (95%CI: 1.29-5.29); income between 500 and 833.33 €, OR = 3.52 (95%CI 1.47-8.47).); planning to start work before the infant was 6 months old, OR = 0.35 (0.19-0.63) . Conclusions The PROLACT intervention in primary care is more effective than the usual practice for maintaining exclusive breastfeeding at 6 months, and can therefore be considered evidence-based practice for implementation in standard practice. Trial registration The trial was registered with ClinicalTrials.gov under code number NCT01869920 (03/06/2013).